Mycobacterial lipopeptides elicit CD4+ CTLs in Mycobacterium tuberculosis-infected humans. - Bruns, Heiko; et al. (Journal of Immunology, 2008)
In searching for immunogenic molecules with the potential to induce protective immune responses against tuberculosis, we developed an ex vivo model to study frequency, phenotype, and effector functions of human T lymphocytes recognizing hydrophobic Ags of Mycobacterium tuberculosis (M.Tb). To obtain unbiased results, we characterized T lymphocytes responding to a crude cell wall extract (chloroform methanol extract of M.Tb (M.Tb-CME)) containing a broad spectrum of mycobacterial glycolipids and lipopeptides. A significant proportion of T lymphocytes recognized M.Tb-CME (290 IFN-gamma+ T cells/10(5) PBMCs) and developed to effector memory cells as determined by the expression of CD45RO and the chemokine receptors CXCR3 and CCR5. Expanded lymphocytes fulfilled all criteria required for an efficient immune response against tuberculosis: 1) release of macrophage-activating Th1 cytokines and chemokines required for the spatial organization of local immune responses, 2) cytolytic activity against Ag-pulsed macrophages, and 3) recognition of infected macrophages and killing of the intracellular bacteria. Phenotypically, M.Tb-CME-expanded cells were CD4+ and MHC class II restricted, challenging current concepts that cytotoxic and antimicrobial effector cells are restricted to the CD8+ T cell subset. Pretreatment of M.Tb-CME with protease or chemical delipidation abrogated the biological activity, suggesting that responses were directed toward mycobacterial lipopeptides. These findings suggest that lipidated peptides are presented by M.Tb-infected macrophages and elicit CD4+ cytolytic and antimicrobial T lymphocytes. Our data support an emerging concept to include hydrophobic microbial Ags in vaccines against tuberculosis.